Analysis Of Nonlinear PID Controller For Tracking Performance Of Ball Screw Drive - Abdullah, Lokman; Anang, Nur Amira; Jamaludin, Zamberi; Chiew, Tsung Heng; Maharof, Madihah; Syed Salim, Syed Najib; Retas, Zain (Penerbit Universiti,UTeM, 2018)
In control system industry, it is crucial to have good tracking performance at higher speed. However, cutting force disturbances in machining affect the performance. Therefore, a good controller is important to compensate the disturbances. The focus area in this paper is to evaluate the tracking performance of Nonlinear PID (NPID) controllers based on two conditions. The first condition is based on a bounded nonlinear gain,